(3MGTjI GdedG TeSG GdLjdGfj Ydi MGTjI GdNaQjs - (3GdLjdGfj (B((3GdcjdGfj(B)(3, GdedG TeSG, eMeO, J (B1098(3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg Pj GdeLO hGdHgGA hGdUdGI hGdSdGe Ydi SjO GdHTQ hGdCfHjGA(B...(3hHYO ajbhd CabQ Ndb Gddg GdZfj eMeO(B...(3gPg eJYdbGJ GJabJ efj HaVd Gddg SHMGfg Ydi eHMK EdGgjGJ GdJLQjO hTQMg GdLOjO(B...s
(3BNQgG (B:s
...(3Hd LejY UaGJg GdLeGdjI cGdYde hGdbOQI hZjQgG Yjf PGJg hgPG ETGQI Edi faj GdcKQI HYO GdPGJ, hGdSdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B609s
(3GdPQjYI(B:(3L(B6(3,U(B49 (340)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds